2019
DOI: 10.1126/science.aat4042
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of commensal antigens by intestinal epithelial cells regulates mucosal T cell homeostasis

Abstract: Commensal bacteria influence host physiology, without invading host tissues. We show that proteins from segmented filamentous bacteria (SFB) are transferred into intestinal epithelial cells (IECs) through adhesion-directed endocytosis that is distinct from the clathrin-dependent endocytosis of invasive pathogens. This process transfers microbial cell wall–associated proteins, including an antigen that stimulates mucosal T helper 17 (TH17) cell differentiation, into the cytosol of IECs in a cell division contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 41 publications
1
106
0
Order By: Relevance
“…Atarashi et al further suggested that the actin reorganisation that is associated with the attachment of SFB to epithelial cells could promote SAA transcription (Atarashi et al, ). A very recent study also links the induction of TH17 cells with SFB‐induced actin rearrangement in epithelial cells (Ladinsky et al, ). This study used electron tomography to analyse the synapse between SFB and epithelial cells and demonstrated that proteins, including the SFBNYU‐03340 immunogenic protein that is targeted by the TH17 response (Yang et al, ), was transferred into epithelial cells trough adhesion‐triggered endocytosis.…”
Section: Mechanisms Of Sfb‐induced Th17 Responses: Lessons From In VImentioning
confidence: 93%
See 2 more Smart Citations
“…Atarashi et al further suggested that the actin reorganisation that is associated with the attachment of SFB to epithelial cells could promote SAA transcription (Atarashi et al, ). A very recent study also links the induction of TH17 cells with SFB‐induced actin rearrangement in epithelial cells (Ladinsky et al, ). This study used electron tomography to analyse the synapse between SFB and epithelial cells and demonstrated that proteins, including the SFBNYU‐03340 immunogenic protein that is targeted by the TH17 response (Yang et al, ), was transferred into epithelial cells trough adhesion‐triggered endocytosis.…”
Section: Mechanisms Of Sfb‐induced Th17 Responses: Lessons From In VImentioning
confidence: 93%
“…Surprisingly, however, inactivation of Cdc42 in epithelial cells only partially impaired the epithelial transcriptomic response induced upon colonisation by SFB, and notably, it did not affect the transcription of genes encoding SAAs or DUOX2. It also failed to impair the IgA response induced by SFB (Ladinsky et al, ). Further studies are, therefore, necessary to delineate the exact role of adhesion‐induced endocytosis and epithelial actin rearrangement in driving the spectrum of immune responses stimulated by SFB.…”
Section: Mechanisms Of Sfb‐induced Th17 Responses: Lessons From In VImentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 This has been hypothesized to occur via mechanosensing of microbial contact, and a recent study has shown that in the case of segmented filamentous bacteria (SFB), the transfer of SFB antigens through IECs via microbial adhesion-triggered endocytosis (MATE) plays a pivotal role. 74 Another recent study shows that epithelial sensing of dietary vitamin A through retinoic acid receptor b is also required for IEC expression of SAAs. 75 Perhaps less appreciated, glucocorticoids (GCs) and neurotransmitters are also abundantly produced by epithelial cells in the gut.…”
Section: Iec Secretion Of Immunomodulatory Moleculesmentioning
confidence: 99%
“…Bacterially derived polysaccharides such as polysaccharide A from B. fragilis, β ‐glucan/galactan polysaccharides from Bifidobacterium bifidum or crude carbohydrate preparations from H. hepaticus can prime Treg or IL‐10 production. Intriguingly, atypical antigen acquisition pathways have also been shown to be important for SFB‐induced Th17 development. Collectively, these studies demonstrate that the intestinal immune system can be activated by a diverse array of microbial taxa through a variety of distinct mechanisms, highlighting a large degree of redundancy in the processes which help to maintain these mutualistic relationships.…”
Section: Of Mice and Menmentioning
confidence: 99%